2015
DOI: 10.1016/j.jnnfm.2015.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Correction of wall adhesion effects in batch settling of strong colloidal gels

Abstract: The batch settling test is widely used to estimate the compressive rheology of strongly flocculated colloidal suspensions, in particular the compressive yield strength and hydraulic permeability. Recently it has been discovered (D.R. Lester et al, J. Rheol., 58(5):12471276, 2014) that wall adhesion effects in these tests may be significantly greater than previously appreciated, which can introduce unbounded errors in the estimation of these rheological functions. Whilst a methodology to solve the underlying st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 35 publications
2
14
0
Order By: Relevance
“…This form captures the experimentally‐observed rapid increase in compressive strength just above gel‐point, along with the progression toward power‐law behavior seen typically at higher concentrations. A power‐law index of n4.0±0.5 seems to be typical of electrolyte‐flocculated and coagulated systems, whereas the strongly polymer‐flocculated CaCO 3 used by Lester et al showed a somewhat higher value of ca. 5.…”
Section: Constitutive Relationships and Modelingmentioning
confidence: 94%
See 2 more Smart Citations
“…This form captures the experimentally‐observed rapid increase in compressive strength just above gel‐point, along with the progression toward power‐law behavior seen typically at higher concentrations. A power‐law index of n4.0±0.5 seems to be typical of electrolyte‐flocculated and coagulated systems, whereas the strongly polymer‐flocculated CaCO 3 used by Lester et al showed a somewhat higher value of ca. 5.…”
Section: Constitutive Relationships and Modelingmentioning
confidence: 94%
“…In each case the default analysis assumes that the unbuoyed self‐weight at any height point z in a sediment of total equilibrium height h eq , viz w(z)=Δρgzheqϕfalse(zfalse)dz, is balanced by the compressive strength at that level, P y ( ϕ { z }): in the above Δ ρ is the suspension inter‐phase density difference, g , the magnitude of the gravitational or centrifugal acceleration and ϕ(z) the local volume‐fraction. The above only holds exactly in the absence of wall adhesion, of course, whereas in its presence a vertical force balance gives dPdz=Δρgϕ4τwD, which shows that otherwise wall effects can only be ignored or neglected when the second term on the RHS is negligible compared to the first, that is, when 4τw(ϕ)DΔρgϕ 1 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since cohesive suspensions, strongly flocculated ones at least, are "ratchet poroelastic" [18] and strain-hardening in effect, the ratio of shear to compressive strength decays from unity at the gel-point to a lower asymptotic value at high volume-fraction. The latter is expected to proportional to the apparent yield strain in shear, defined as, γ Y app = (σ Y ) / G [19,20], and where the yield stress σ Y could either be the true yield stress or the adhesive, depending upon the context (e.g. whether any bounding surfaces are rough or smooth).…”
Section: -Practical and Processing Implicationsmentioning
confidence: 99%
“…whether any bounding surfaces are rough or smooth). It is of interest to ask how this apparent yield strain, which turns out to be convenient and compact way of the parameterizing the importance or otherwise of wall or shear effects in solid-liquid separation [19,20], compares with the true yield strain. It should be fairly obvious that γ Y app ≥ γ bond in the present terms, where the latter is the critical strain above which softening occurs: equal in the absence of the kind of strain hardening shown in fig.…”
Section: -Practical and Processing Implicationsmentioning
confidence: 99%